Engineered core-shell magnetic nanoparticle for MR dual-modal tracking and safe magnetic manipulation of ependymal cells in live rodent - Peng, Y; Lui, C; Chen, Y; Chou, S; Pi-Tai, C; Yung, K; Tsang, E (IOP Publishing, 2017)
Tagging recognition group(s) on superparamagnetic iron oxide is known to aid localization (imaging), stimulation and separation of biological entities using magnetic resonance imaging (MRI) and magnetic agitation/separation (MAS) techniques. Despite the wide applicability of iron oxide nanoparticle in T2-weighted MRI and MAS, the quality of image and safe manipulation of exceptionally delicate neural cells in a live brain are currently the key challenges. Here, we demonstrate the engineered manganese oxide clusters-iron oxide core-shell nanoparticle as a MR dual-modal contrast agent (DMCA) for the applications in neural stem cells imaging and magnetic manipulation in live rodent. As a result, using this engineered nanoparticle and associated technologies, identification, stimulation and transportation of labelled potentially multipotent neural stem cells from a specific location of a live brain to another by magnetic means for self-healing therapy can therefore be made possible.